Increasing the yield of drip-irrigated rice by improving photosynthetic performance and enhancing nitrogen metabolism through optimizing water and nitrogen management - Zhao, Lei; Tang, Qingyun; Song, Zhiwen; Yin, Yongan; Wang, Guodong; Li, Yuxiang (Frontiers in Plant Science, 2023)
Drip irrigation under plastic film mulching is an important technique to achieve water-conserving and high-efficiency rice (Oryza sativa L.) production in arid areas, but the grain yield of drip-irrigated rice is much lower than the expected yield (10.9-12.05 t·hm-2) in practical production applications. Therefore, we hope to further understand the photosynthetic physiological mechanism of drip-irrigated rice yield formation by optimizing water and nitrogen management during the growth period and provide a scientific reference for improving yield and nitrogen use efficiency (NUE) of drip-irrigated rice in arid areas. In 2020 and 2021, T-43 (a drought-resistant; V1) and Liangxiang-3 (a drought-sensitive cultivar; V2) were cultivated under two water treatments (W1: limited drip irrigation, 10200 m3·hm-2; W2: deficit drip irrigation, 8670 m3·hm-2) and three nitrogen fertilization modes with different ratios of seedling fertilizer:tillering fertilizer:panicle fertilizer:grain fertilizer (N1, 30%:50%:13%:7%; N2, 20%:40%:30%:10%; and N3, 10%:30%:40%:20%). The photosynthetic characteristics, nitrogen metabolism, yield, and NUE were analysed. The results showed that compared with other treatments, the W1N2 resulted in 153.4-930.3% higher glutamate dehydrogenase (GDH) contents and 19.2-49.7% higher net photosynthetic rates (Pn) in the leaves of the two cultivars at 20 days after heading, as well as higher yields and NUE. The two cultivars showed no significant difference in the physiological changes at the panicle initiation stage, but the Pn, abscisic acid (ABA), indole acetic acid (IAA), gibberellic acid (GA3), and zeatin riboside (ZR) levels of V1 were higher than those of V2 by 53.1, 25.1, 21.1, 46.3 and 36.8%, respectively, at 20 days after heading. Hence, V1 had a higher yield and NUE than V2. Principal component analysis revealed that Pn and GDH were the most important physiological factors affecting rice yield performance. In summary, the W1N2 treatment simultaneously improved the yield and NUE of the drought-resistant rice cultivar (T-43) by enhancing the photosynthetic characteristics and nitrogen transport capacity and coordinating the balance of endogenous hormones (ABA, IAA, GA3, and ZR) in the leaves.